Investigating ultrasonic wave dispersion and attenuation in fresh cementitious materials: A combined numerical, analytical, and experimental approach. (December 2018) - Iliopoulos, S.N.; De Smet, L.; Aggelis, D.G.
Abstract: The heterogeneity of cement-based materials and the severe wave-microstructure interactions at the fresh state render the thorough investigation of ultrasonic wave propagation imperative, especially when the latter is used for material characterization and quality control. In this study, parallel to the advanced ultrasonic wave dispersion and attenuation experiments, numerical simulations are also performed offering faster, reliable and accurate solutions at low cost, as well as flexibility on the design and measured properties. Cement pastes and mortars are investigated and the observed dispersive and attenuative trends are further explained with scattering theories reinforcing the characterization potential. The results pinpoint air bubbles and sand grains as causes of the dispersion and attenuation frequency dependent trends. The distinct frequency regimes where these phenomena are observed allow for the more accurate characterization of the microstructure. For the first time, the strong qualitative and quantitative agreement between experiments, scattering theories, and numerical simulations provides holistic insights into wave propagation in fresh cementitious materials and firmly connects the dispersion and attenuation of waves to their origin.